IDENTIFIKASI KESULITAN MAHASISWA FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI SURABAYA DALAM PENYELESAIAN STUDINYA - Amira Agustin Kocimaheni; Zainul Aminin; Ajeng Dianing Kartika (Universitas Negeri Surabaya, 2020)
The study completion in undergraduate program (S1) requires the completion of thesis writing for students. The flow of thesis preparation at the Faculty of Languages and Arts (FBS), Universitas Negeri Surabaya (Unesa), has followed the Thesis Writing Guidebook issued by FBS Unesa. In the manual, the requirements and procedures for writing a thesis are clearly written. But even so, there are still many students who have not been able to complete their thesis writing on time, which hinders the completion of their studies. Therefore, it is necessary to identify students' difficulties in completing their studies, especially at the thesis writing stage. From the results of the distribution of research instruments in the form of questionnaires, it was concluded that there were five categories of difficulties faced by students, namely: 1) Difficulties in submitting / selecting research titles, 2) Difficulties in the consultation process, 3) Difficulties in data collection and processing, 4) Difficulties in the examination process, and 5) Difficulty in the revision process.